Positive solutions to a system of psi-Riemann–Liouville fractional differential equations with coupled boundary conditions - Tudorache, Alexandru; Luca, Rodica (Nonlinear Analysis: Modelling and Control, 2026)
We investigate the existence of positive solutions for a system of ψ-Riemann–Liouville fractional differential equations with positive parameters and sign-changing nonlinearities subject to nonlocal coupled boundary conditions containing Riemann–Stieltjes integrals and fractional derivatives of various orders. To prove our main result, we use the nonlinear alternative of Leray–Schauder type.